Validation of an empirical formula for use in multi-objective optimization study of a tanker for optimal EEOI - Ng, Keng Fu (2019)
This report attempts to validate the use of a semi-empirical formula for use in multiobjective optimization study. Experiment and empirical data from various commonly found ship types will be extracted and calculated respectively. These data will then be plotted against either wave heading of Froude number. The corresponding plot will then be used to analyze and compare the two results to validate the empirical formula’s use.